WBG COVID-19 Crisis Response Operational Update : Delivering on the WBG Twin Goals in an Era of Compounding Crises - World Bank (Washington, DC, 2022)
This note provides an update on the WBG’s COVID-19 Crisis Response, outlined in June 2020 to help developing countries address the impacts of the pandemic while maintaining a line of sight to long-term development goals. It comprises five short sections: (I) the impacts of COVID-19 and compounding crises on developing countries, (II) an update on the WBG’s operational crisis response and priorities moving forward, (III) the critical role of international coordination, (IV) WBG financing framework for GRID, and (V) concluding remarks.